Application of Linear Body Measurements for Predicting Weaning and Yearling Weight of Bali Cattle - Gunawan, A; Jakaria, Jakaria (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
The objective of this research was to predict the weaning and yearling weight of Bali cattle using simple linear body measurement. The height wither (HW), body length (BL) and heart girth (HG) were measured in centimeters, using caliper, whereas weaning (WW)and yearling weight (YW) was determined in kilograms using a weighing scale. Results of the correlation coefficient showed Â that hearth girth (HG) highly correlated with weaning and yearling weight were 0.847 and 0.871 respectively. In all, the height wither (HW) had the least correlation coefficient were 0.328 and 0.782 on weaning and yearling weight respectively.Â Results of the stepwise regression showed that HG was a good estimator of WW and YW of Bali cattle followed by HW and BL. The comparison of residuals indicated that only two equations (HG and BL) accurately predicted weaning and yearling weight. From these results, it was concluded that weaning and yearling weight of Bali cattle can be estimated using simple linear body measurement of heart girth, body length and height wither especially in most remote areas where farmers are challenged with the unavailability of weighing scale. (Animal Production 12(3): 163-168 (2010)Key Words: weaning and yearling weight, linear body measurements, Bali cattle